Parliaments and Poverty in Africa - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, reminded participants that it is important to remember the more than 1 billion people worldwide struggling to survive on less than $1 a day. Fighting the scourge of poverty is at the heart of the World Bank Group’s mission. The burden of debt and the disease of corruption threaten to undermine the efforts to meet the Millennium Development Goals. Many regions of the world have made significant progress to improve living standards and reduce poverty. Sub-Saharan Africa is moving dangerously in the opposite direction. Africa’s richest resource, and its best hope, is its people. But more development financing and debt relief is needed. In the long run, neither aid nor debt relief will help the poor escape poverty without a transparent and accountable government. We are seeing an informed African citizenry demanding change. The World Bank Group is committed to supporting champions of reform in both government and civil society. Partnering with parliaments from donor countries is as important as working with parliaments in recipient countries. To achieve true prosperity for our integrated planet, we must work together to help give the poorest among us the chance to find their way out of poverty.